Renegotiating Disciplinary Fields in the Life Sciences - Minelli, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Recent and ongoing debates in biology and the philosophy of biology reveal a widespread dissatisfaction with traditional explanatory frameworks. There are also problems with the current definitions or circumscriptions of key concepts such as gene, species, and homology, and even of whole disciplinary fields within the life sciences, e.g. developmental biology. These contrasting views are arguably a symptom of the need to revisit traditional, unchallenged partitions between the specialist disciplines within the life sciences. In the diversity of topics addressed and approaches to move beyond the current disciplinary organization, the five essays in this volume will hopefully stimulate further exploration towards an improved articulation of life sciences.